Accuracy of Routine Prenatal Genetic Screening in Patients Referred for Genetic Counseling - Gilstrop Thompson, Marisa; Corsetti, Stephanie; Jain, Vanita; Ruhstaller, Kelly; Sciscione, Anthony (American Journal of Perinatology, 2020)
Objective The American College of Obstetricians and Gynecologists (ACOG) guidelines recommend routine prenatal screening for genetic diseases that could affect the pregnancy. We sought to determine the rate of missed genetic information in the general obstetrician's routine prenatal genetic screening process.Study Design This is a sequential case series of women referred for genetic counseling between March and August of 2015. Once identified, all women completed a personalized genetic history/exposure intake form (GHEF) created by our certified genetic counselors, followed by an in-person genetic counseling session with pedigree generation. The corresponding prenatal record was reviewed for genetic history obtained by the referring provider, most often utilizing the standardized ACOG prenatal intake form's genetic and family history sections. This information was then compared with that discovered in the GHEF and through the in-person genetic counseling session. Missed genetic information was defined as information discovered on the GHEF or during the in-person genetic counseling session which was not noted on the prenatal genetic screening document from the obstetric provider. Missing genetic information that lead to a change in clinical care, either through additional laboratory screening tests, fetal imaging or prenatal diagnostic testing through chorionic villus sampling, or amniocentesis was considered significant. We also assessed the study population as to maternal race, parity, and referral source. Statistical significance was assessed using Chi-squared testing with p < 0.05 identifying significance.Results A total of 299 patients underwent genetic counseling. Of them, 57.5% patients were referred from private providers, 28.1% from academic faculty practice, and 14.4% from a federally funded clinic. Missed genetic information was discovered in 171/299 (57.2%) of patients in the genetic counseling process. Of these 171 patients, 28.7% were identified via the GHEF and 52.6% during the in-person genetic counseling session. Of the 171 patients who had new genetic information discovered, 73 (42.7%) findings were significant. There was no statistical difference in patient race or referring office setting in the occurrence of new information found.Conclusion In our population, genetic history obtained in the general obstetrician's office, regardless of practice type, missed genetic information in over half of cases with approximately 40% of that information leading to a subsequent change in clinical care. Developing a genetic intake form similar to our pregenetic counseling form, or modification/clarification of the “Family History and Genetic Screening” section within the standardized ACOG prenatal genetic history form, used at most practices in our region may decrease missed genetic information in the general obstetrician's office.
Keywords: genetic counseling; antenatal care; generalist